2006
DOI: 10.5070/v422110148
|View full text |Cite
|
Sign up to set email alerts
|

Field Test of GonaCon™ Immunocontraceptive Vaccine in Free-Ranging Female White-Tailed Deer

Abstract: Locally overabundant deer herds, particularly those inhabiting fenced or other enclosed areas in urban or suburban settings, are presenting serious problems for wildlife managers, landowners, and the general public. Traditional methods of population control, such as regulated harvest by licensed hunters, often are impractical or illegal in such settings. The development of safe and effective wildlife contraceptives is needed to control locally overabundant populations in situations where traditional management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In a 7-year review of GonaCon studies in various species (using AdjuVac as the adjuvant), Miller et al (2008) state "The most common report is that there is no visible injection site reaction, or that there is a non-visible but palpable lump underneath the skin at the site of the injection." Two field studies using the same vaccine in white-tailed deer resulted in similar findings as well as "considerable injection-site reaction deep in the muscle" when the site was dissected (Gionfriddo et al 2006). These findings are similar to ours where injection site reactions were more readily visible during necropsy.…”
Section: Discussionsupporting
confidence: 85%
“…In a 7-year review of GonaCon studies in various species (using AdjuVac as the adjuvant), Miller et al (2008) state "The most common report is that there is no visible injection site reaction, or that there is a non-visible but palpable lump underneath the skin at the site of the injection." Two field studies using the same vaccine in white-tailed deer resulted in similar findings as well as "considerable injection-site reaction deep in the muscle" when the site was dissected (Gionfriddo et al 2006). These findings are similar to ours where injection site reactions were more readily visible during necropsy.…”
Section: Discussionsupporting
confidence: 85%
“…Efficacy data will be required for the end-use formulation. This requirement will be met by submission of data from pen studies with white-tailed deer at Pennsylvania State University (Miller et al 2000;Miller and Killian 2001) and from a field trial conducted in Maryland under Good Laboratory Practices (Gionfriddo et al 2006). The pen studies showed 90-100% effectiveness in reducing fertility during the first year and~70% effectiveness during the second year.…”
Section: Development and Registration Of Gonaconmentioning
confidence: 99%
“…), it appears that if a visible reaction occurs, it is because there has been a previous T cell response to a killed bacteria in a vaccine, or the animal has a bacterial infection which can cause the T cell response to our vaccine. In two field studies with white-tailed deer, there were no visible injection site reactions on the surface; however, when the injection site is dissected, there was considerable injection-site reaction deep in the muscle (Gionfriddo 2006). This is in contrast to the target safety study at Penn State (Killian et al 2006b), where there was no visible injection-site reaction and the granulomas at the dissected injection site were minimal.…”
Section: Injection Site Reactionsmentioning
confidence: 86%